HLA-DR expression on monocytes is decreased in polytraumatized patients. Issue 1 (December 2015) - Vester, Helen; Dargatz, P.; Huber-Wagner, S.; Biberthaler, P.; Griensven, M.
Abstract Background Sepsis, systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome (MODS) remain the most frequent causes of complications and death in severely injured patients. A main reason for the development of these syndromes is a post-traumatic dysregulation of the immune system. Several studies in intensive care unit (ICU) patients could detect a pivotal role of HLA-DR expression on monocytes. So far, its importance for development of SIRS, sepsis or MODS in the severely injured patient is not clear. Methods Therefore, we have analysed HLA-DR expression on monocytes from severely injured patients (ISS > 16) during the post-traumatic course, which was on the day of trauma, as well as on days 3, 7 and 14 post trauma. Clinical data were analysed and the HLA-DR expression levels of patients who developed post-traumatic sepsis, SIRS or MODS were compared to those with a more favourable outcome. Young and healthy volunteers as well as patients undergoing prosthetic hip replacement after trauma were enrolled as control groups. HLA-DR molecules on monocytes were marked with PE-conjugated antibodies and the mean fluorescence intensity (MFI) was analysed via flow cytometry. Results 24 severely injured patients (mean age 34 ± 2.7 years) mainly after high energy motor vehicle accidents as well as 8 controls (total hip replacement) and 9 healthy volunteers (mean age 26.2 ± 1.2 years) were enrolled. A total of eight patients suffered from sepsis (33.3 %) (six males, two females) and 17 patients suffered from SIRS (70.9 %) (10 males, 7 females). MODS was present in five patients (20.8 %), three male and two female patients. In four of these five patients the MODS developed subsequent to sepsis. HLA-DR expression significantly decreased after trauma and slowly returned to normal after 14 days, irrespective of the complications developed. Conclusion In conclusion, post-traumatic HLA-DR expression on monocytes is significantly reduced after multiple trauma and it is back to normal on day 14. No significant changes in HLA-DR expression on monocytes from severely injured patients suffering from SIRS, MODS or sepsis compared to those who did not have complications could be detected. Nevertheless, HLA-DR expression on monocytes may be used to identify the immunological pro- or anti-inflammatory phase the patient is going through.